2021
DOI: 10.1126/scisignal.abe4509
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2 controls the activity of PKC and Akt by phosphorylating a conserved TOR interaction motif

Abstract: The complex mTORC2 is accepted to be the kinase that controls the phosphorylation of the hydrophobic motif, a key regulatory switch for AGC kinases, although whether mTOR directly phosphorylates this motif remains controversial. Here, we identified an mTOR-mediated phosphorylation site that we termed the TOR interaction motif (TIM; F-x3-F-pT), which controls the phosphorylation of the hydrophobic motif of PKC and Akt and the activity of these kinases. The TIM is invariant in mTORC2-dependent AGC kinases, is ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 133 publications
0
47
1
Order By: Relevance
“…HM phosphorylation enhances phosphorylation at the A-loop and increases Akt activity whereas TM phosphorylation induces dephosphorylation of A-loop phosphorylation, thus decreasing Akt activity [39]. A recent study identified additional mTORC2-regulated phosphorylation sites termed TOR interacting motif (TIM) at the C-terminal tail [40]. These sites are conserved among AGC kinases (Akt1-T443, Akt-T444, Akt3-T440) and regulate A-loop phosphorylation by PDK1.…”
Section: Structural Heterogeneity and Regulation Of Akt Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…HM phosphorylation enhances phosphorylation at the A-loop and increases Akt activity whereas TM phosphorylation induces dephosphorylation of A-loop phosphorylation, thus decreasing Akt activity [39]. A recent study identified additional mTORC2-regulated phosphorylation sites termed TOR interacting motif (TIM) at the C-terminal tail [40]. These sites are conserved among AGC kinases (Akt1-T443, Akt-T444, Akt3-T440) and regulate A-loop phosphorylation by PDK1.…”
Section: Structural Heterogeneity and Regulation Of Akt Isoformsmentioning
confidence: 99%
“…These sites are conserved among AGC kinases (Akt1-T443, Akt-T444, Akt3-T440) and regulate A-loop phosphorylation by PDK1. Although there are controversies whether mTORC2 directly phosphorylates HM site or not, it can regulate Akt activity by phosphorylating TIM [40].…”
Section: Structural Heterogeneity and Regulation Of Akt Isoformsmentioning
confidence: 99%
“…Following their biosynthesis, conventional PKC isozymes are processed by a series of constitutive phosphorylations that are necessary for the enzymes to adopt an autoinhibited and stable conformation [ 7 ]. These priming phosphorylations are mediated by mTORC2 at a recently identified TOR Interaction Motif and adjacent turn motif on the C-tail, promoting phosphorylation by the phosphoinositide-dependent kinase 1 (PDK1) at the activation loop, in turn triggering an intramolecular autophosphorylation at another key regulatory site in the C-tail, the hydrophobic motif [ 11 ]. In the autoinhibited state, PKC is relatively resistant to dephosphorylation and subsequent degradation, and it has a half-time on the order of days [ 12 ].…”
Section: Pkc Maturation and Signalingmentioning
confidence: 99%
“…Although each AGC kinase is regulated in unique ways by phosphorylation, the assembled Ct-Tail and the ways that it contributes to stabilizing the N-lobe of the kinase core when it is in its active conformation is conserved. The ways in which mTORC contributes to the assembly of the PKC Ct-Tail and the newly discovered TIM motif in the Ct-Tail is just the newest chapter to a long story (Baffi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%